The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1007/bf00545676
|View full text |Cite
|
Sign up to set email alerts
|

Selective grazing by the mud snail Ilyanassa obsoleta

Abstract: Mud snails (Ilyanassa obsoleta) starved for 48 h were allowed to feed on sediments in laboratory microcosms. Sediment cores sliced at 2 mm intervals were compared to snail stomach contents for per cent carbon and nitrogen, plant pigment contents and species composition of benthic diatoms. Concentrations of carbon, nitrogen, phaeopigments, phycocyanin and chlorophyll were enriched in the top 2 mm of the sediments compared to 7-10 mm depth by a factor of 2-10. In turn, these materials were 20-40 times more conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 31 publications
1
22
0
2
Order By: Relevance
“…Its diet can be varied, but probably is mainly confined to deposit feeding (e.g. Curtis & Hurd 1981, Connor & Edgar 1982. The genus Hydrobia has a similar main diet (Newel1 1965, Lopez & Kofoed 1980 and is occasionally as abundant as in the European Atlantic and North Sea region (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its diet can be varied, but probably is mainly confined to deposit feeding (e.g. Curtis & Hurd 1981, Connor & Edgar 1982. The genus Hydrobia has a similar main diet (Newel1 1965, Lopez & Kofoed 1980 and is occasionally as abundant as in the European Atlantic and North Sea region (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrobia populations are commonly at densities where resource limitation by food availability is likely (Fenchel & Kofoed 1976, Levinton & Lopez 1977. I. obsoleta is efficient at grazing and digestion of diatoms (Pace et al 1979, Connor & Edgar 1982, the principal source of food for Hydrobia (Fenchel & Kofoed 1976, and seems to be far more effective at reducing microalgal standing stocks than H, totteni . However, significant as it may seem, this effect may be minor relative to interference effects.…”
Section: Introductionmentioning
confidence: 99%
“…갯벌 내 대표적인 생산자로 저서미세조류는 퇴적물 섭 식자의 직접적인 먹이원일 뿐만 아니라 (Connor and Edgar 1982;Hughes and Sherr 1983), 재부유되어 부유 섭식자에게도 중요한 먹이원이 된다 (Baillie and Welsh 1980). 또한 재부유된 저서미세조류의 생체량과 생산력이 수층 내 식물플랑크톤보다 높게 나타나는 경우도 있다 (Varela and Penas 1985;Lukatelich and McComb 1986;de Jonge and van Beusekom 1995).…”
Section: 서 론unclassified
“…He suggested that detritus-feeders augment their C uptake when detritus supply is low by eating benthic algae. The relative importance of microphytobenthos may be much greater for at least a few of the key marsh invertebrates, such as gastropods (Pace et al 1979, Lopez and Kofoed 1980, Conner and Edgar 1982, Lopez-Figueroa and Neill 1987, shrimp (R.I.E. Newell and B. Bebout, unpublished data) and mussels (D.A.…”
Section: Quantitative Importance Of Different Trophic Pathwaysmentioning
confidence: 99%
“…Observational studies have shown that gastropods, such Melampus bidentatus, Littorina irrorata, Ilyanassa obsoleta, and Hydrobia ulvae do feed on epiphytic and epibenthic algae (Wetzel 1976, Barnes 1989. A variety of reports suggest that these snails preferentially select and digest surface-associated algae, which often comprise the bulk of material in their guts (Pace et al 1979, Lopez and Kofoed 1980, Conner and Edgar 1982, Lopez-Figueroa and Neill 1987. Recent work by and Newell and Porter (this volume) indicate that 3 to 28% of the biomass of senescent cordgrass is composed of fungi and that this fungal component is efficiently utilized by gastropods (Newell and Bärlocher 1993, Newell and Porter, this volume).…”
Section: Herbivoresmentioning
confidence: 99%